PENGENDALIAN MANAJEMEN ANALISIS SISTEM PENGENDALIAN MANAJEMEN UNTUK MENINGKATKAN EFISIENSI, EFEKTIVITAS DAN EKONOMISASI (Studi Kasus Pada Koperasi Simpan Pinjam Niaga Central Abadi Wates Kediri) - Ramayanti, Eryska; Srihastusi, Eni (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2016)
Analysis Of Management Control Systems To Improve The Efficiency, Effectiveness, Ekonomisasi (Case Study On The savings and credit Cooperatives Niaga Central Abadi Wates, Kediri) aiming to find out the influence of management control systems towards greater efficiency, effectiveness and ekonomisasi partially or simultaneously. The methods used in this research is a method of multiple linear regression analysis using statistical tests and statistical tests T F. The results showed that management control systems are simultaneously effect significantly to efficiency and effectiveness but not significant effect against the ekonomisasi. Management control system partially effect significantly to efficiency and effectiveness to the value significance of 0.036 and 0.009 but not significant effect against the ekonomisasi with the value significance of 0.212. Keywords: management control systems, efficiency, effectiveness and ekonomisasi.